Venture Investment Incentive Mechanisms and Simulation with Venture Entrepreneurs Having Multistage Efforts Based on Fairness Preference Theory - Kaihong Wang; Chuan Ding; Jiacheng Chen; Aimin Li (Discrete Dynamics in Nature and Society)
When venture capital has been invested into venture companies, venture capitalists and venture entrepreneurs form a principal-agent relationship. Take into account the fact that the venture entrepreneur’s effort is a long process, because the effort is not the same at different stage. Therefore, efforts variables are seen as the multistage dynamic variable, and venture investment principal-agent model with venture entrepreneurs having multistage efforts is constructed on the basis of the classic principal-agent theory in the paper. Further, in the later stage effort of venture entrepreneurs is affected by the size of prestage benefit with venture capitalists and venture entrepreneurs; thus the fairness preference model is improved, and venture investment principal-agent model with venture entrepreneurs having multistage efforts is constructed on the basis of fairness preference theory. Both theoretical derivation and simulation have demonstrated that, under the condition of information asymmetry, if the fairness preference of venture entrepreneurs holds, then (1) venture capitalists provide venture entrepreneurs with level higher than that without fairness preference, (2) in every single stage venture entrepreneurs make efforts higher than those without fairness preference, and (3) in two periods both venture investors and venture entrepreneurs gain total real gains higher than those in two periods without fair preference.